Detailed Analysis of the Palmomental Reflex and Its Clinical Significance - Benxu Ma; Jianying Zhang; Yanlei Cui; Huanmin Gao (Brain and Behavior)
ABSTRACT Purpose This comprehensive review thoroughly explores the clinical significance of the palmomental reflex (PMR) in neurological disorders. PMR is a primitive reflex that, when reemerging in adults, indicates underlying neurological dysfunction. Method The article elaborates on the clinical assessment techniques, neurophysiological basis, and applications of PMR in various neurological disorders, including neurodegenerative diseases, cerebrovascular disorders, traumatic brain injury, and multiple sclerosis. Finding By understanding the modulation and suppression mechanisms of PMR, valuable insights into the specific neurological impairments associated with these disorders can be gained. Conclusion The potential of PMR as a diagnostic marker, prognostic indicator, and treatment monitoring tool is increasingly evident.